Cirugía de catarata senil y su efecto en la calidad de vida (2021)
Senile cataract is a clouding of the lens caused and associated with advanced age; It is the most frequent and important cause of preventable blindness in adults worldwide and its prevalence has increased, given the rate that people's life expectancy does. It affects visual acuity, contrast sensitivity among other functions,¿ influencing people's quality of life, even limiting interaction with their environment, associated with feelings of isolation, depression and anxiety. The technological and surgical advances for its treatment, make it considered an easy-to-handle pathology, the difficulties of access and availability of visual health services, in some countries, causes deficiencies to be found in its diagnosis and treatment.